Evaluation of rs37464444 Polymorphism of miR-499 Gene in Patients with Colon Cancer Compared with Healthy Subjects - Behjat Kalantari Khandani; Sara Shafieipour; Amir Mobasserfar; Mohammad Javad Zahedi; Mohammad Hashemi; Mohammad Mahdi Hayatbakhsh Abbasi; Sodaif Darvish Moghadam (Journal of Kerman University of Medical Sciences, 2020)
Background: Single nucleotide polymorphisms (SNPs) have been introduced as a new genomic source for cancer. Therefore, it was decided to conduct a study to evaluate the rs3746444 polymorphism of miR-499 in patients with colon cancer in comparison with healthy subjects. Methods: This case-control study was conducted to investigate rs3746444 polymorphism of miR-499 in blood samples of case and control groups. Patients with a confirmed diagnosis of cancer based on pathologic report were enrolled in the study as the case group and compared with healthy subjects. The level of significance was considered at p < 0.05. Result: The mean of DNA count in samples was 63.17± 23.51 that was significantly higher in the case group. The rs3746444 polymorphism of miR-499 was significantly higher in patients with cancer compared to the healthy subjects (P < 0.05). Conclusion: In this study, rs3746444 polymorphism of miR-499 was significantly higher in patients with colon cancer, which indicated that people with this polymorphism had a higher risk for malignancy.